PENGARUH KEMAMPUAN MENDENGARKAN DAN MENCATAT TERHADAP PRESTASI BELAJAR KIMIA - Das Salirawati (Universitas Negeri Yogyakarta, 2008)
The aim of this study was to know whether there was any positive and significant relationship between the ability of effectively listening and recording learning material and the chemistry study achievement of students of MAN Maguwoharjo Yogyakarta. The study was designed as of one sample and three variables. The population was designated to be all the students of class X semester 2 MAN Maguwoharjo Yogyakarta it the academic year of 2006/2007 consisting of 96 students. Sixty-four students were taken as the subjects by cluster random sampling for two classes (class XB and XC). The free variable was effective listening and recording in chemistry classes, and the binding variable was chemistry study achievement of the students. Three instruments were utilized; namely a questionnaire of listening ability, a value sheet of the recording books, and a test of chemistry study achievement. The data were analyzed by double regression and yielded an Ry(1,2) of 0.546. The first and second grade correlation coefficients (r1-2) were 0,393 and 0.369, respectively. The significance test yielded a value of F of 12,933 against the F table of 3.148 on the significance level of 5% with the df of 2 versus 61. The statistics showed that there was a positive and significant relationship between the ability of effectively listening and recording of chemistry matter, either separately or together, on the chemistry study achievement of the students. The relative contributions of the ability of effective listening on the chemistry study achievement were 53,05% and 15,80, The effective contributions of the ability of effective recording on the chemistry study achievement were 46,95% and 13,98%.